Effect of ultrasound in the bonding process of MB8/Cu/2024 dissimilar alloys - Yinan LI; Xiaoxuan YUAN; Dingwen SHI; Zilong PENG (Hanjie xuebao)
Ultrasonic-assisted transient liquid phase (U-TLP) bonding was used to realize the fast and reliable bonding of MB8/Cu/2024 dissimilar alloys in air. The joining process was divided into three stages, solid/solid interface stage-acoustic-induced stripping of metal particles and removal of oxide films, solid/liquid transformation stage-frictional heat generation of solid interface led to appearance of reactive liquid phases and liquid/liquid interface reaction stage- ultrasonic accelerated interfacial reaction in liquid. The results showed that in the solid/solid interface stage, the longitudinal ultrasound can cause relative displacement in the x- direction and y-direction on the interfaces of MB8/Cu and 2024/Cu. And under the influence of shear stress, This displacement could lead to interfacial friction, resulting in the removal of Al and Cu particles and partial removal of the oxide film. in the solid/liquid transformation stage, 2024/Cu interface produced a temperature rise due to friction under the action of ultrasound, and Al2Cu + α-Al liquid phase began to appear after the eutectic reaction temperature was reached; In the liquid/liquid interface reaction stage, cavitation and acoustic streaming effects made MB8/Cu and 2024/Cu interfaces generate z-direction displacement field and acoustic pressure field, accelerating generation of Al2Cu + α-Al and Mg2Cu + α-Mg eutectic phases to form joining. the maximum shear strength of the MB8/2024 dissimilar metal joints was 64 MPa.